Jangva 10 - Galleria Jangva, Helsinki (Helsinki : Galleria Jangva Helsinki, 2004)
Markula, Juha ; Mattsson, Matti ; Claeson, Stig ; Keinänen, Maire ; Laukkanen, Riitta ; Tapaninen, Malla ; Bergvik, Annika ; Granlund, Carina ; Rabb, Hannele ; Mallander, J.O. ; Valtonen, Mikko ; Korpi, Anne-Mari ; Poijärvi, Marjo ; Metsähonkala, Mikko ; Penttilä, Matti ; Jokinen, Kalevi ; Haglund, Bo ; Cajander, Veli-Risto ; Vesalahti, Mika ; Maja, Anu ; Kaukanen, Tiina ; Aromaa, Anna ; Häggblom, Bia ; Judin, Susanna ; Holopainen, Juha ; Holmlund, Christina ; Skants, Sanna ; Seppälä, Mika ; Eronen, Outi ; Puhakka, Kirsti ; Landin, Harri ; Kuusisto, Ari ; Purhonen, Pekka ; Pennttilä, Terhi ; Ala-Maunus, Petri ; Enckell, Daniel ; Merimaa, Henry ; Kujansuu, Erja ; Lindström, Björn B. ; Huber, Mona ; Katajisto, Katarina ; Pynnä, Ilpo ; Hämäläinen, Tommi-Tapio ; Wilenius, Petri Johannes ; Oldenburg, Claes ; Paik, Nam June ; Valtonen, Mikko ; Partanen, Timo ; Turvanen, Leena ; Pirilä, Sirpa ; Tukiainen, Jussi ; Jääskeläinen, Soile ; Mäkelä, Sirkku ; Talja, Minna ; Hallikainen, Mikko ; Pyykkö, Sirpa ; Hynninen, Sirpa ; Miettinen, Sirpa ; Pirilä, Sirpa ; Tallberg, Monica ; Hukkataival, Helinä ; Tuokkko, Kirsti ; Paunu, Paavo ; Suonpää, Visa ; Kiviniemi, Petri ; Turunen, Johanna ; Gröhn-Soininen, Reetta ; Palmgren, Dan ; Mäki, Nonna-Nina ; Ala-Harja, Sirkku ; Leppänen, Juha ; Nurro, Arto ; Hämäläinen, Antti ; Hautamäki, Piia ; Kangas, Leena ; Tolvanen, Mirja ; Keuro, Mari ; Blomqvist, Marianne ; Toikkanen, Pertti ; Kärkkäinen, Reijo ; Persson, Jan-Kenneth ; Hautajärvi, Harri ; Hirvikoski, Sirpa ; Haanperä, Jari ; Enckell, Daniel ; Oksman, Henni ; Schakir, Tülay ; Rahikainen, Micke ; Zitting, Marina ; Gebhard, Hannu ; Kallio, Mikko ; Vesala, Reika ; Vesala, Tuomas ; Akimoto, Koichi ; Tukiainen, Jussi ; Pynnä, Ilpo ; etc.
Exhibitions 1994-1997 p. 10-16
Exhibitions 1998-2004 p. 22-70
Other Activities 1994-2003 p. 76-93
Engels, Fins
boek